Biomimicry for Sustainable Innovation: The Answers Are All Around Us. (15th April 2018) - GaleWyrick, Seth
Abstract : Trying to design a new and sustainable solution to a human problem? Chances are some other species has already done it for you. Got a design problem? Biomimicry offers solutions that are elegant as well as sustainable.